Tissue-Specific Gene Repositioning by Muscle Nuclear Membrane Proteins Enhances Repression of Critical Developmental Genes during Myogenesis - Robson, Michael I.; de las Heras, Jose I.; Czapiewski, Rafal; Lê Thành, Phú; Booth, Daniel G.; Kelly, David A.; Webb, Shaun; Kerr, Alastair R.W.; Schirmer, Eric C. (Molecular cell, 2016)
Whether gene repositioning to the nuclear periphery during differentiation adds another layer of regulation to gene expression remains controversial. Here, we resolve this by manipulating gene positions through targeting the nuclear envelope transmembrane proteins (NETs) that direct their normal repositioning during myogenesis. Combining transcriptomics with high-resolution DamID mapping of nuclear envelope-genome contacts, we show that three muscle-specific NETs, NET39, Tmem38A, and WFS1, direct specific myogenic genes to the nuclear periphery to facilitate their repression. Retargeting a NET39 fragment to nucleoli correspondingly repositioned a target gene, indicating a direct tethering mechanism. Being able to manipulate gene position independently of other changes in differentiation revealed that repositioning contributes ⅓ to ⅔ of a gene’s normal repression in myogenesis. Together, these NETs affect 37% of all genes changing expression during myogenesis, and their combined knockdown almost completely blocks myotube formation. This unequivocally demonstrates that NET-directed gene repositioning is critical for developmental gene regulation. [Display omitted] •Tissue-specific NETs direct repositioning of critical muscle genes during myogenesis•Expression changes for NET-repositioned genes depend on cell differentiation state•Isolating position from differentiation reveals its contribution to gene expression•Three NETs together affect 37% of all genes normally changing in myogenesis Muscle-specific nuclear envelope transmembrane proteins (NETs) optimize myogenic gene expression by physically recruiting genes to the periphery and enhancing their repression. Specifically manipulating the position of endogenous genes in myoblasts and myotubes indicates that peripheral localization enhances repression, but only in context of other changes in differentiation.